A STUDY OF AWARENESS AMONG RURAL WORKING WOMEN REGARDING FINANCIAL INCLUSION SCHEMES (CAHIERS MAGELLANES-NS, 2024)
Financial inclusion is the access to valuable and affordable financial products and services by every individual and business that can meet their needs, like transactions, payments, savings, credit, and insurance (World Bank,2022). It aims to provide vulnerable people inexpensive and timely access to financial services, eventually reducing financial exclusion and boosting economic growth (Gupta, 2017).  Financial inclusion has been on the government's priority list since the recognition of financial exclusion, especially with implementing various programs and initiatives to close the gap between unbanked and banked populations. Awareness of financial inclusion is essential, as it refers to how well people are informed about the availability and benefits of financial products and services. The adoption and use of financial initiatives and their overall impact are significantly influenced by individual awareness. Despite the increased emphasis, awareness of financial inclusion schemes remains a concern, particularly in rural and underserved areas. This lack of awareness may eventually prevent people from connecting to financial institutions, resulting in low participation and limited use of financial services.